Probing neutrino mass with multilepton production at the Tevatron in the simplest R-parity violation model - Magro, Mauricio Bernardino; De Campos, Fernando [UNESP]; Éboli, Oscar J. P.; Porod, Werner; Restrepo, Diego; Valle, José W. F. (Springer Nature, 2003)
We analyse the production of multileptons in the simplest supergravity model with bilinear violation of R parity at the Fermilab Tevatron. Despite the small .R-parity violating couplings needed to generate the neutrino masses indicated by current atmospheric neutrino data, the lightest supersymmetric particle is unstable and can decay inside the detector. This leads to a phenomenology quite distinct from that of the R-parity conserving scenario. We quantify by how much the supersymmetric multilepton signals differ from the R-parity conserving expectations, displaying our results in the m0 ⊙ m1/2 plane. We show that the presence of bilinear R-parity violating interactions enhances the supersymmetric multilepton signals over most of the parameter space, specially at moderate and large m0. © SISSA/ISAS 2003.
Keywords: Beyond Standard Model; Solar and Atmospheric Neutrinos; Supersymmetry Phenomenology